2021
DOI: 10.1002/bin.1836
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of verbal responses using instructive feedback: A replication and extension

Abstract: Few studies have investigated the potential of instructive feedback (IF) procedures to result in the emergence of novel-related verbal responses. Furthermore, few studies have directly assessed the role self-echoic behavior may have in IF procedures. The current replication and extension evaluated the effects of IF procedures during unmastered primary target trials on the emergence of novel verbal responses. All learners acquired primary, secondary, and related, but unpresented, verbal responses, and maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…A novel target is demonstrated in the previous example, where the instructor taught the student to identify a feature of a bird and then demonstrated a letter sound within the IF procedure. Previous research has demonstrated that secondary targets that share a relation to the primary targets (e.g., expansion target) have resulted in the emergence of responses under intraverbal control (Frampton & Shillingsburg, 2020 ; Gavidia et al, 2022 ; Tullis et al, 2021 , 2022 ). In addition, researchers have observed the emergence of secondary targets that do not share a relation to the primary targets (i.e., novel target) when the target response is under tact control (Nottingham et al, 2020 ) and intraverbal control (Vladescu & Kodak, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…A novel target is demonstrated in the previous example, where the instructor taught the student to identify a feature of a bird and then demonstrated a letter sound within the IF procedure. Previous research has demonstrated that secondary targets that share a relation to the primary targets (e.g., expansion target) have resulted in the emergence of responses under intraverbal control (Frampton & Shillingsburg, 2020 ; Gavidia et al, 2022 ; Tullis et al, 2021 , 2022 ). In addition, researchers have observed the emergence of secondary targets that do not share a relation to the primary targets (i.e., novel target) when the target response is under tact control (Nottingham et al, 2020 ) and intraverbal control (Vladescu & Kodak, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of secondary targets may result in more rapid learning because learners can acquire twice (or more; Nottingham et al, 2017 ) the number of targets when IF is included (Shillingsburg et al, 2018 ). Acquisition of secondary targets with IF has been demonstrated in 1:1 and small-group instruction for several populations, including individuals of typical development and individuals with disabilities like intellectual disability, ASD, speech and language impairments, learning disabilities, developmental delays, and Down syndrome (e.g., Carroll & Kodak, 2015 ; Leaf et al, 2017 ; Nottingham et al, 2017 ; Nottingham et al, 2020 ; Tekin-Iftar, 2003 ; Tullis et al, 2022 ; Werts et al, 1995 ). Secondary target acquisition with IF has also been demonstrated with several procedural variations such as the number, location, and presentation schedule (Carroll & Kodak, 2015 ; Nottingham et al, 2017 ; Nottingham et al, 2020 ; Vladescu & Kodak, 2013 ).…”
mentioning
confidence: 99%